2020
DOI: 10.1111/jcmm.15873
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions and clinical applications of exosomal long non‐coding RNAs in cancer

Abstract: Exosomes are microvesicles that are derived from multivesicular bodies (MVBs) and released into the extracellular space upon fusion of MVBs with the plasma membrane. 1 Exosomes contain multiple components including lipids, proteins, RNA and DNA. Exosomes take part in the intercellular communication by transferring cargoes from donor cells to recipient cells. One of the cargoes of exosomes is long non-coding RNA (lncRNA). LncRNAs are RNA transcripts longer than 200 nt and have limited protein-coding potential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 108 publications
(168 reference statements)
0
22
0
Order By: Relevance
“…In recent years, accumulating evidence has revealed fundamental roles of lncRNAs in the regulation of numerous physiological and pathological processes, such as cell differentiation, proliferation and apoptosis, and the initiation and progression of human cancer. [9][10][11] At present, it is widely acknowledged that numerous lncRNAs are involved the progression of DLBCL. For example, lncRNA SMAD5-AS1 inhibited proliferation of DLBCL as a ceRNA of to increase APC expression and limiting Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, accumulating evidence has revealed fundamental roles of lncRNAs in the regulation of numerous physiological and pathological processes, such as cell differentiation, proliferation and apoptosis, and the initiation and progression of human cancer. [9][10][11] At present, it is widely acknowledged that numerous lncRNAs are involved the progression of DLBCL. For example, lncRNA SMAD5-AS1 inhibited proliferation of DLBCL as a ceRNA of to increase APC expression and limiting Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that ncRNAs can be transferred between cells through exosomes [ 24 ]. Similarly, this study investigated whether uc.189 could form exosomes and transfer them from ESCC cells to HLECs.…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes release into the extracellular milieu influences cellular morphology by interfering with cell signaling components and by modulating recipient gene expressions and functions and the cell differentiation program. Exosomes have been reported to influence infections [ 91 , 92 , 93 ], tumor development and metastasis [ 94 , 95 , 96 , 97 , 98 ], neurodegenerative diseases [ 99 , 100 , 101 , 102 ], inflammation, and autoimmune disorders [ 103 , 104 , 105 , 106 ]. In addition, they play crucial role in intracellular communication and in the pathogenesis of several diseases as they can transfer signals (cytokines, proteins, lipids, nucleic acids, and infectious agents) from cells to nearby or distant locations [ 91 , 107 , 108 ].…”
Section: Immunomodulatory Effect Of Exosomesmentioning
confidence: 99%